Forward genetic screening in engineered colorectal cancer organoids identifies regulators of metastasis - Xin Wang; Zvi Cramer; Nicolae Adrian Leu; Keara Monaghan; Kayla Durning; Stephanie Adams-Tzivelekidis; Joshua H. Rhoades; Jonathan Heintz; Yuhua Tian; Joshua Rico; Diego Mendez; Ricardo Petroni; et al. (Proceedings of the National Academy of Sciences, 2025)
Metastatic outgrowth requires that cancer cells delaminate from the primary tumor, intravasate, survive in circulation, extravasate, migrate to, and proliferate at a distal site. Recurrent genetic drivers of metastasis remain elusive, suggesting that unlike the early steps of oncogenesis, metastasis drivers may be variable. We develop a framework for identifying metastasis regulators using CRISPR/Cas9-based screening in a genetically defined organoid model of colorectal adenocarcinoma. We conduct in vitro screens for invasion and migration alongside orthotopic, in vivo screens for gain of metastasis in a syngeneic mouse model. We identify CTNNA1 and BCL2L13 as bona fide metastasis-specific suppressors which do not confer any selective advantage in primary tumors. CTNNA1 loss promotes cell invasion and migration, and BCL2L13 loss promotes anchorage-independent survival and non-cell-autonomous changes to macrophage polarization. This study demonstrates proof of principle that large-scale genetic screening can be performed in tumor-organoid models in vivo and identifies novel regulators of metastasis.